A Feasibility Study on Burnplast - Florendo, Michael L.; Galang, Myrtle Holiday; Mendoza, Philip Basil (Diliman, Quezon City College of Engineering, 2003)
The feasibility of the new product BurnPlast dressing for burns was evaluated in this study. BurnPlast is a medical product derived from carrageen and it promises a better treatment for burn wounds and injuries. This dressing in addition to its very low price relative to conventional treatments was also proven to provide faster and more rapid healing. The overall feasibility of BurnPlast was segmented into three main aspects, namely market, technical and financial. In the market segment, analysis on the potential demand for the product showed that the primary clients and customers were government hospitals. Moreover, it was also realized that BurnPlast has huge potential in entering the commercial market. With careful analysis on factors such as competitors and distribution channels and the formulation of an effective market strategy, BurnPlast was concluded to be very marketable. For the technical aspect of the study, operational process procedures, materials, equipment, facility and organizational design were the focus of analysis. Under decisions made on this segment, the overall production and operational details for the product were established and conclusions on technical feasibility were drawn. The center of the financial study was estimating the overall cost of undertaking the operations of producing and selling the BurnPlast dressing and how to finance it. From this phase, it was determined that the investment cost of starting this project amounts to P28 million with a return on investment of 4.99. The optimal form of financing was found to be a mix of debt and equity. Lastly, a social profitability analysis was also conducted which identified the overall benefits and costs of the product to society and the nation. A net benefit a=valued at P33 million was projected contribution to the economy and society for the initial 5-year operation of BurnPlast production.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Wounds and injuries--Treatment.; Burns and scalds; Carrageenan; Participatory monitoring and evaluation (Project management)